A batch delivery mechanism of network update in software‐defined wide area networks. Issue 3 (6th September 2021) - Zhang, RongBo; Li, Xin; Niu, Jibin; Wang, Yinqing
Summary: In software‐defined network (SDN) architecture, the network decisions are all located on a logically centralized controller. Based on installing rules into switches of the data plane, the controller directly initiates and schedules a network update and which will cause a delay in the completion time of a network update. The situation is aggravated in wide area networks (WANs) further due to the switches deployed in a wide geographical area bring long propagation delay. On account of adopting the in‐band transmission style to deliver control messages instead of dedicated control channels is economics in WANs, the retransmission of control messages causing by congestion of the data channels is another unbearable delay source. This paper describes a new control information batch delivery mechanism (CIBDM) of network updates to relieve the delay and enhance the reliability of control message transmission in SD‐WANs. The characteristics of the novel scheme include the following: (1) every control information message may contain multiple update information of different forwarding devices, and each update information consists of a set of update instructions with dependencies; (2) by using a similar mechanism of onion routing, in the delivering process of control messages, it attains the security for each control rule of the specified devices; (3) with delegating the update consistency coordination into the data plane, it improves network update on the completion time. A comprehensive evaluation runs on 10 network topologies selected from all over the world. Experimental results show that CIBDM achieves rapid network updates with reliable message transmission. Abstract : Control information batch delivery mechanism (CIBDM) is proposed for relieving the delay and enhancing the reliability of control message transmission in SD‐WANs. Every control information message may contain multiple update information and update constraints of different forwarding devices based on a multiplexing scheme, with delegating the update consistency coordination into the data plane, improving network update on the completion time. By using a similar mechanism of onion routing, the transfer of updates attains security.